New Architecture of Foreign Direct Investment Regulation in the European Union - D. E. Moiseeva; A. D. Kulinich (Vestnik MGIMO-Universiteta)
This article examines current trends in financial governance within the European Union (EU), focusing on the regulation of foreign direct investment (FDI). The adoption of supranational mechanisms for EU FDI screening through Regulation 2019/452 not only highlights the expansion of multi-level governance, as promoted by the European Commission, but also reconfigures the EU's role as a global actor in investment transactions. This shift directly impacts a wide range of stakeholders.The study aims to explore the institutional architecture established by Regulation 2019/452 and address the research question: Why has the EU transitioned from a neoliberal approach favoring free capital movement (negative integration) to a framework emphasizing common European monitoring rules (positive integration)? The theoretical framework combines the concept of multi-level governance and securitization theory, underpinned by new institutionalism, which facilitates an analysis of how institutions, particularly the European Commission, articulate and advance common interests within political frameworks. The findings reveal that the securitization of Chinese FDI served as a critical tool for the Commission to legitimize its push for supranational regulation. Regulation 2019/452 is identified as “entry-level legislation,” designed to be amended through its built-in revision mechanism, ultimately broadening the Commission’s exclusive competencies in this area. This trajectory was partially confirmed by the Commission’s January 2024 proposal to strengthen the Regulation. The analysis situates this shift within a broader global context, demonstrating how the EU's move from neoliberalism to protectionism mirrors trends in other major economies, such as the United States, China, and India, all of which employ FDI monitoring mechanisms. The article also identifies key events that acted as catalysts for the EU’s geopolitical reassessment of foreign investment—from a stance of openness to recognizing potential threats to collective security and public order. It draws a parallel with the Commission’s use of securitization discourse in the energy sector, which contributed to the partial communitarization of energy policy through multi-level governance.